Community-Based Ecological Learning through Indigenous Conservation - Qoriah Rahmawati; Asep Muhyidin; Aan Asphianto; Ujang Jamaludin (FITK UIN Walisongo Semarang, 2025)
The integration of indigenous knowledge into sustainability education has attracted increasing scholarly attention; however, existing studies mainly conceptualize indigenous traditions as sources of cultural values or contextual learning resources, providing limited explanation of the pedagogical mechanisms through which ecological responsibility develops within community life. This study investigates the Ngaruat Leuweung Titipan tradition in an indigenous community in Lebak Regency, Banten, Indonesia, to explain how indigenous conservation functions as a community-based ecological learning process. A qualitative educational ethnography design was employed using participant observation, semi-structured interviews, and document analysis involving customary leaders, community members, youth representatives, and a local teacher. Data were analysed through thematic analysis and mechanism synthesis. The findings identify four interconnected pedagogical mechanisms: ecological worldview formation, participatory ecological knowledge transmission, collective social regulation, and intergenerational ecological internalization. These mechanisms demonstrate that ecological responsibility is cultivated through sustained participation in culturally embedded conservation practices rather than formal instruction alone. The study extends ethnopedagogy, Traditional Ecological Knowledge, and Education for Sustainable Development by proposing indigenous conservation as a community-based pedagogical process that strengthens culturally responsive sustainability education